Sistema IoT para el monitoreo de variables climatológicas en cultivos de agricultura urbana - Chanchí-Golondrino, Gabriel-Elias; Ospina-Alarcón, Manuel-Alejandro; Saba, Manuel (Revista Científica, 2022)
Based on the growing trend of urban agriculture, this work aims to build an IoT system for the monitoring and analysis of climatological variables of interest in urban agriculture crops. The methodology considered for conducting this research comprises four phases: selection of tools and technologies, design of the IoT system architecture, construction of the system’s prototype, and a case study in the context of lettuce crops. As a result of this research, an IoT system based on open hardware and software tools was built, which is articulated within the conventional 4-layer IoT architecture (capture, storage, analysis, and visualization). With respect to the existing solutions, the advantage of this system is the use of portable SBC platforms, as well as the inclusion of machine learning models within the analysis layer. From the case study, conducted on a home lettuce crop, it is concluded that the selected tools allow capturing, monitoring, and analyzing climatological variables of interest in urban agriculture crops. Likewise, it is concluded that the studied analysis models can be customized by considering the agroclimatic characteristics of each crop and that they are useful for decision-making related to crop physiology.